Integration of character education in constructivism-based learning model: its impact on students’ mathematics learning outcomes - Astutik, Heny Sri; Rahman, Abd; Nurwati Djam’an (Universitas Terbuka, 2025)
This study investigates the effectiveness of a constructivist mathematics learning model that incorporates character education in improving students’ understanding of mathematical concepts. This research uses a quantitative approach with a quasi experimental design. This study involved students from 3 schools, who participated in 5 integrated learning sessions and uses a paired sample t-test to evaluate the effect of the integrated learning model on students' understanding of mathematics concepts. Data analysis was conducted using inferential statistical techniques. Based on the results of the paired samples test on the pretest and postest scores, it shows that Sig value. (1-tailed) 0.000 < 0.05 and tcount = 58.539 > 1.673 means that significantly the average student learning outcomes after being taught with an integrated constructivism-based learning model of character education are better than before being taught with an integrated constructivism-based learning model of character education. The results of this study show that the integration of character education in the learning model creates a more interactive, reflective and value-based learning experience, which ultimately contributes to improved understanding of mathematical concepts. Furthermore, this study also offers practical recommendations for educators and policy makers in designing learning models that are more adaptive and oriented towards student character development.